Using a blended learning instructional strategy to support students’ civic knowledge and social skills: A strategy to support rural schools in East Timor - Olugbenga IGE; Thuthukile Jita (Ukrainian Journal of Educational Studies and Information Technology)
Timor-Leste began re-engineering the educational system after suffering the effects of a drawn-out struggle to attain independence. Despite the opportunities provided for out-of-school children to enlist in the new education system, and the projects bankrolled by international organizations, teachers in rural schools in Timor-Leste are confronted with teaching and learning-related challenges. This paper presents the outcomes of an experiment on the usability of blended learning instructional strategy to support students’ civic knowledge and social skills. A pretest-posttest quasi experimental design was used to evaluate the usability of a Blended Learning Instructional Strategy on 52 secondary school students in the junior cadre in rural areas in Nigeria. The data analysis suggested that the combination of blended learning and conventional lecture method has the capacity of inculcating civic knowledge and social skills in learners in rural schools. The research determined the trajectories of male and female learners’ performance using their academic abilities after being taught civic concepts and socially-related skills with conventional teaching methods and computer-assisted teaching. The results from the Nigerian study were used to present best practices for citizenship and social development teachers in using a blended learning instructional strategy in rural schools in Timor-Leste. However, further research is recommended on using a blended learning instructional strategy in Timor-Leste and other developing nations.